Internal challenges of adoption of e-procurement in higher education institutions in Uganda: A case of Makerere University. - Watuleke, Joseph (IJRDO- Journal of Educational Research, 2017)
E-procurement has been widely recognized for carrying the potential to significantly increase thebuyers’ and sellers’ benefits. The Deutsche Bank research (Meyer, 2011) established that a fulltransition to e-procurement could generate savings of between 50 billion and 70 billion Euro.Earlier research had shown that the extent of e-procurement infrastructure integration betweenorganizations had a direct impact on the savings and benefits obtained by an organization (Minand Galle, 2003). Implying that lack of or poor integration of e-procurement infrastructurelowered benefits and could increase costs, while a good integration had yielded the oppositeeffect. As a result of this promise, business today has focused on the supply function to a greaterextent than it previously did (Purchase & Dooley, 2005).E-procurement which has been offered varied interpretations simply refers to the process ofpurchasing goods and services electronically required for an organization’s operation (Mitchell,2000). It involves electronic interaction between or among parties involved in the procurementprocess rather than physical exchange or contact. While there are an array of opportunities andadvantages e-procurement offers, adoption of e-procurement systems in organizations especiallyHigher education institutions is not happening as quickly as predicted. User organizations arefaced with a complex decision to make as to whether along to digitalize their purchases andprocurement function or remain traditional (Davila, Gupta & Palmer, 2003). Some reasons havebeen presented by researchers to explain the delayed adoption of e-procurement by many oforganizations. While some organizations have opted to adopt a ‘wait and see’ approach to eprocurement,others are faced with a complexity of decision resulting from an array of softwareprograms available on market (Osmonbekov, Bello and Gilliland, 2002).